Influence Of Dormitories Lighting On Digital Eye Strain Among University Students - Sahmalla, Vinothan (2025)
Inadequate lighting in dormitory rooms may significantly impacts visual comfort and contributes to digital eye strain (DES) among university students. This study aims to assess the effect of dormitory lighting conditions on the prevalence and severity of DES. A cross-sectional study was conducted to measure the illuminance levels in hostel rooms using a lux meter, as well as to evaluate uniformity ratios based on the Guidelines on OSH for Lighting at Workplace. A structured and validated questionnaire was distributed via Google Forms to 307 students, collecting data on socio-demographic information, digital device usage habits, and symptoms of DES. The finding revealed that the measured illuminance levels ranged from 64.07 ± 8.99 lux to 73.52 ± 8.79 lux, which are below the recommended standard of 100 lux of rest room. In contrast, the uniformity levels ranged from 0.76 ± 0.04 to 0.79 ± 0.04, which met the guideline requirements. The most frequently reported symptoms of DES included headaches (74.6%), eye dryness (68.4%), and neck, shoulder, or back pain (73.9%). A chi-square analysis showed that age, gender, educational level, and the brightness of devices were significantly associated with Dry Eye Syndrome (DES). Simple logistic regression further indicated that illuminance level and uniformity had significant relationships with symptoms such as eye burning, eye itching, heavy eyelids, and eye fatigue. Additionally, a multiple logistic regression analysis revealed that only gender and device brightness significantly influenced DES, accounting for a variation of 25.9% after controlling for potential confounding factors. These findings highlight that inadequate lighting conditions in dormitory rooms may contribute to DES. To reduce DES and improve visual comfort among students, it is recommended to enhance lighting conditions and raise awareness about preventive measures.